Conjugation of gold nanoparticles and recombinant human endostatin modulates vascular normalization via interruption of anterior gradient 2–mediated angiogenesis. Issue 7 (July 2017) - Pan, Fan; Yang, Wende; Li, Wei; Yang, Xiao-Yan; Liu, Shuhao; Li, Xin; Zhao, Xiaoxu; Ding, Hui; Qin, Li; Pan, Yunlong
Several studies have revealed the potential of normalizing tumor vessels in anti-angiogenic treatment. Recombinant human endostatin is an anti-angiogenic agent which has been applied in clinical tumor treatment. Our previous research indicated that gold nanoparticles could be a nanoparticle carrier for recombinant human endostatin delivery. The recombinant human endostatin–gold nanoparticle conjugates normalized vessels, which improved chemotherapy. However, the mechanism of recombinant human endostatin–gold nanoparticle–induced vascular normalization has not been explored. Anterior gradient 2 has been reported to be over-expressed in many malignant tumors and involved in tumor angiogenesis. To date, the precise efficacy of recombinant human endostatin–gold nanoparticles on anterior gradient 2–mediated angiogenesis or anterior gradient 2–related signaling cohort remained unknown. In this study, we aimed to explore whether recombinant human endostatin–gold nanoparticles could normalize vessels in metastatic colorectal cancer xenografts, and we further elucidated whether recombinant human endostatin–gold nanoparticles could interrupt anterior gradient 2–induced angiogenesis. In vivo, it was indicated that recombinant human endostatin–gold nanoparticles increased pericyte expression while inhibit vascular endothelial growth factor receptor 2 and anterior gradient 2 expression in metastatic colorectal cancer xenografts. In vitro, we uncovered that recombinant human endostatin–gold nanoparticles reduced cell migration and tube formation induced by anterior gradient 2 in human umbilical vein endothelial cells. Treatment with recombinant human endostatin–gold nanoparticles attenuated anterior gradient 2–mediated activation of MMP2, cMyc, VE-cadherin, phosphorylation of p38, and extracellular signal–regulated protein kinases 1 and 2 (ERK1/2) in human umbilical vein endothelial cells. Our findings demonstrated recombinant human endostatin–gold nanoparticles might normalize vessels by interfering anterior gradient 2–mediated angiogenesis in metastatic colorectal cancer.